Students' characteristics of students' obstacles in understanding the definition of a function. (March 2019) - Jannah, U R; Nusantara, T; Sudirman; Sisworo
Abstract: Prior knowledge and experience on the concept of definition's function gave an important rule on the students' understanding. Their prior knowledge about function relate to their understanding of sets, ordered pairs, Cartesian product, and relations. Since a concept of function is the concept related to another topics, it will develop new knowledge about the formal definition of a function. Students' obstacle in understanding those concepts rose because they found some complicacy in connecting their prior knowledge to the recent one. This research is a case study to characterize the student's obstacles in understanding those concepts to form a formal definition of a function. The subjects of this research were four out of nineteen students based on the criteria specified. The result showed that there were two characteristics, namely refung present as the first characteristic and hirefung present as the second characteristic. This study makes easier to create teaching learning process based on characteristics of students' obstacles. It can be a references for lecturers to arrange a learning trajectory based on the features of students' obstacles.